Pemanfaatan Pembelajaran ICT Dalam Optimalisasi Proses Belajar Mengajar Guru SMP - Arief Nugroho Wibowo; Agus Supandi; Andri Andri; Sigit Widiyarto (Jurnal Pengabdian UntukMu NegeRI, 2020)
The development of information technology and telecommunications greatly affected the world of education. By utilizing technology, education would be more advanced and not be left behind. Not only that, the teaching and learning process would be more effective, efficient, interesting and fun. Unfortunately, not all teachers were able to use technology as a learning medium. SMP N 8 Bekasi is a junior high schools located in Bekasi. Distance from the city of Bekasi to the government center (Jakarta) was about 20 km. With the distance that was not too far, the utilization of technology in the world of education should be very high. But the reality was different. the use of technology to help the teaching and learning process is still very minimal. Especially computers as learning media. This was because the skills in operating a computer were still very minimal. From the results of the situation analysis, what was needed by the teachers in the three schools is ICT (Information Communication Technologies) training. The training was specifically for the operation of some software that could help teachers in the learning process. Some of these software include power point, excel, macromedia flash, and movie maker.